Real-world experience with the IUB Ballerine MIDI copper IUD: an observational, single-centre study in Israel. (2nd January 2020) - Baram, Ilan; Aharon, Arnon; Klein, Rinat; Shkolnik, Ketty
Abstract: Objective: The aim of the study was to assess the acceptability of the intrauterine ball IUB Ballerine MIDI copper intrauterine device (IUD), using real-world data collected from users and physicians in Israel. Methods: In this retrospective, observational study, conducted in a single clinic in Israel, healthy women ( n  = 175) who had had the device inserted ≥12 months prior to enrolment, and their physician, completed questionnaires relating to device insertion, user experience and performance. Results: The mean age at insertion was 32.8 ± 6.7 years; most women were married (80.6%) and multigravid (89.1%). At the time of the study, 131 (74.9%) women were still using the device; in 13 cases (7.4%), premature removal was due to desire to conceive. The 12 month continuation rate, excluding the women seeking to conceive, was 90.1%. The expulsion rate was 3.4% ( n  = 6) and the pregnancy rate was 0.57% ( n  = 1). Most of the women still using the device reported no to moderate pain or cramps (90.0%) and moderate to high (72.6%) satisfaction with the device; 76.3% said they would recommend it to friends and relatives. Most of the insertion procedures (86.9%) were uneventful and none required cervical dilation. Conclusion: The IUB Ballerine MIDI raised no major safety concerns and was both effective and highly accepted in a cohort of women, covering a broad age range, treated in a gynaecology clinic in Israel.